7 Dynamic changes of injured myocardium very early after acute myocardial infarction quantified using t1 mapping cardiovascular magnetic resonance technique. (May 2018) - Alkhalil, Mohammad; Borlotti, Alessandra; De Maria, Giovanni Luigi; Gaughran, Lisa; Langrish, Jeremy; Lucking, Andrew; Ferreira, Vanessa; Kharbanda, Rajesh K; Banning, Adrian P; Channon, Keith M; Dall'Armellina, Erica; Choudhury, Robin P
Abstract : Introduction: Recent data have suggested that myocardial oedema followed bimodal pattern early post ST-segment elevation myocardial infarction (STEMI). Yet, there was disagreement between oedema quantified by cardiac magnetic resonance (CMR) imaging and tissue desiccation. Using highly-sensitive T1 mapping we sought to study the temporal changes in the extent and intensity of injured myocardium within one week post STEMI. Methods: A first group (n=31) underwent three 3 T-CMR scans (time-point (TP) <3 hours, 24 hours and 6 days) using T1-mapping. A second group (n=17) had a single scan at 24 hours using both T1-mapping and T2-weighted sequences to assess the extent of area-at-risk (AAR) measured by these techniques. Results: The mean T1 relaxation time value within the AAR of the first group was reduced after 24 hours (p<0.001 for TP1 vs TP2) and subsequently increased at 6 days (p=0.041 for TP2 vs TP3). However, the extent of AAR quantified using T1-mapping did not follow the same course, and no change was detected between TP1 and TP2 (p=1.0) but between TP2 and TP3 (p=0.019). In the second group where both T1-mapping and T2-weighted were compared, extent of AAR was significantly larger on T1-mapping (42%±15% vs 39±15%, p=0.025). Conclusion: The intensity of oedema post-STEMI followed a bimodal pattern; while the extent of AAR did not track the same course. This discrepancy has implications for use of CMR in this context and may explain the previously reported disagreement between oedema quantified by imaging and tissue desiccation.